Identification of memory kernels in heat flow measuring heat flux at the ends of the bar - Pais, Enno (Mathematical Modelling and Analysis, 2010)
An inverse problem to determine time‐ and space‐dependent relaxation kernels of internal energy and heat flux with first kind boundary conditions by means of heat flux measurements is considered. The case when observations of the heat flux are made at the ends of the bar with thermal memory was not studied before. Existence and uniqueness of a solution to the inverse problem are proved. The financial support of Estonian Science Foundation is gratefully acknowledged (Grant nr. 7728). First published online: 10 Feb 2011